Metabolomics of Neurotransmitters and Related Metabolites in Post-Mortem Tissue from the Dorsal and Ventral Striatum of Alcoholic Human Brain - Kashem, Mohammed Abul; Ahmed, Selina; Sultana, Nilufa; Ahmed, Eakhlas U; Pickford, Russell; Rae, Caroline; Šerý, Omar; McGregor, Iain S; Balcar, Vladimir J (Neurochemical research, 2016)
We report on changes in neurotransmitter metabolome and protein expression in the striatum of humans exposed to heavy long-term consumption of alcohol. Extracts from post mortem striatal tissue (dorsal striatum; DS comprising caudate nucleus; CN and putamen; P and ventral striatum; VS constituted by nucleus accumbens; NAc) were analysed by high performance liquid chromatography coupled with tandem mass spectrometry. Proteomics was studied in CN by two-dimensional gel electrophoresis followed by mass-spectrometry. Proteomics identified 25 unique molecules expressed differently by the alcohol-affected tissue. Two were dopamine-related proteins and one a GABA-synthesizing enzyme GAD65. Two proteins that are related to apoptosis and/or neuronal loss (BiD and amyloid-β A4 precursor protein-binding family B member 3) were increased. There were no differences in the levels of dopamine (DA), 3,4-dihydrophenylacetic acid (DOPAC), serotonin (5HT), homovanillic acid (HVA), 5-hydroxyindoleacetic acid (HIAA), histamine, L-glutamate (Glu), γ-aminobutyric acid (GABA), tyrosine (Tyr) and tryptophan (Tryp) between the DS (CN and P) and VS (NAc) in control brains. Choline (Ch) and acetylcholine (Ach) were higher and norepinephrine (NE) lower, in the VS. Alcoholic striata had lower levels of neurotransmitters except for Glu (30 % higher in the alcoholic ventral striatum). Ratios of DOPAC/DA and HIAA/5HT were higher in alcoholic striatum indicating an increase in the DA and 5HT turnover. Glutathione was significantly reduced in all three regions of alcohol-affected striatum. We conclude that neurotransmitter systems in both the DS (CN and P) and the VS (NAc) were significantly influenced by long-term heavy alcohol intake associated with alcoholism.
Keywords: Human brain; Corpus Striatum; lidé; Humans; Tandem Mass Spectrometry; alkoholismus; Alcoholism; posmrtné změny; Postmortem Changes; Metabolomics; corpus striatum; Neurotransmitter Agents; vysokoúčinná kapalinová chromatografie; metabolomika; kalibrace; Neurotransmitter; tandemová hmotnostní spektrometrie; Liquid chromatography/tandem mass spectrometry; Calibration; neurotransmiterové látky; Chromatography, High Pressure Liquid; Alcohol; Striatum